A new measurement method and comparison analysis of mechanical impedance of a tool-hand system - Książek, M. A.; Tarnowski, J. (Archives of Acoustics, 2006)
In the paper the stand experimental studies of the hand-handle-tool system have been done with high speed camera application. The applied measurement devices and computer analysis of the data allowed for estimation of force and velocity of handle and finally for calculation of mechanical driving point impedance of the system.